Cloning of phytase gene from Aspergillus niger 563 and its expression in E.coli system - Geetha, S.; Kumar, K. K.; Arul, L.; Kokiladevi, E.; Balasubramanian, P.; Sudhakar, D. (International Journal of Environment, Agriculture and Biotechnology, 2023)
A phyA was cloned from Aspergillus niger by reverse transcription polymerase chain reaction. The amplified 1404 bp fragment was cloned in a T/A cloning vector and confirmed by sequencing. The isolated phytase gene showed 99.0 % sequence identity at nucleotide and protein level with Aspergillus niger CBS 513.88 phytase. The amino acid sequence from the phyA cDNA contained the consensus motifs, RHGXRXP and HD which are conserved among histidine acid phosphatases. The phytase cDNA was subcloned in pET28a(+) expression vector and expressed in E. coli. The expression of the gene was confirmed through SDS-PAGE analysis. A 52 kDa protein as per the calculated molecular mass of the translational product of phytase gene was observed in crude lysate of E. coli culture induced with IPTG. The protein was purified using nickel based His-bind resin column and checked on SDS-PAGE. The purified recombinant enzyme showed a single band of 52 kDa protein. The phytase activity of pET-phyA IPTG induced E. coli culture and purified phytase was 383.5 U/ml and 826.33 U/ml, respectively.